2012
DOI: 10.15288/jsad.2012.73.44
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Extroversion as Moderators of the Association Between Alcoholics Anonymous and Sobriety

Abstract: Objective: Although women make up one third of Alcoholics Anonymous (AA) membership, research on gender and AA has been limited. Findings in the literature are mixed, with few empirical investigations of factors that may moderate any gender differences found. AA is highly interpersonal, and research has found that women are more extroverted than men. The current study explores the impact of AA on sobriety, gender differences in the relationship between AA and sobriety, and whether extroversion can inform our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Some have speculated that women may not identify as well as men with 12-Step programs, in part because women may resist the notion of powerlessness and surrender based on their historically subservient status in society (Hillhouse & Fiorentine, 2001; Krentzman, Brower, Cranford, Bradley, & Robinson, 2012; Matheson & McCollum, 2008; Timko, 2008). Others have suggested that women may be more likely to identify with the 12-Step approach because of their tendency toward lower self-esteem, an external locus of control, and a greater willingness to admit their mistakes and to disclose negative things about themselves (Beckman, 1994; Kaskutas, 1994; Timko, 2008).…”
Section: Special Populations—who May Need More or Different Help?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some have speculated that women may not identify as well as men with 12-Step programs, in part because women may resist the notion of powerlessness and surrender based on their historically subservient status in society (Hillhouse & Fiorentine, 2001; Krentzman, Brower, Cranford, Bradley, & Robinson, 2012; Matheson & McCollum, 2008; Timko, 2008). Others have suggested that women may be more likely to identify with the 12-Step approach because of their tendency toward lower self-esteem, an external locus of control, and a greater willingness to admit their mistakes and to disclose negative things about themselves (Beckman, 1994; Kaskutas, 1994; Timko, 2008).…”
Section: Special Populations—who May Need More or Different Help?mentioning
confidence: 99%
“…There may be a number of factors that arise in the course of such discussions. As an example, some individuals, such as agnostics or atheists, are put off by the focus on the concept of a “Higher Power,” spirituality, and perceived religiosity (Tonigan, Miller, & Schermer, 2002); others, particularly women, may have concerns with the focus on “ powerlessness” (Kaskutas, 1994; Krentzman et al, 2012); whereas others, particularly those who have social phobia and/or a tendency to avoid attachments may find being in groups and the concept of joining a “fellowship” anxiety provoking (Jenkins & Tonigan, 2011; Tonigan et al, 2010). It is also important to address real barriers that make meeting attendance difficult, such as time, travel/transportation, and child care needs.…”
Section: What Can Social Workers and Professionals Do To Help?mentioning
confidence: 99%
“…Studies using timeline follow-back assessment approaches allow for a more detailed look into specific risks associated with incidents of violence at the daily level (Chermack et al, 2010; Epstein-Ngo et al, 2012). Yet, to date, most studies using timeline follow-back methodology have been conducted for adult substance use (Brower et al, 2011, Chermack et al, 2010; Krentzman et al, 2012; Tweedly et al, 2012), for adult violence and substance use (Chermack et al, 2010), or for adolescent substance use and dating violence (Epstein-Ngo et al, 2012; Rothman et al, 2012). This method has not been used to examine factors associated with incidents of substance use and peer violence at the daily level, and no prior work has described in detail the type of substances used that preceded the incident of victimization or aggression among adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Post-release AA attendance is associated with improved drinking outcomes for women leaving jail 9 , as well as in community samples 1014 . Furthermore, because they are free and widely available 15 , twelve step programs, including Alcoholics Anonymous (AA), can successfully overcome many post-release barriers to services.…”
Section: Introductionmentioning
confidence: 94%